Beyond Linguistic Gaps: Types of Code-Switching Among Jordanian Bilingual speakers - Al Yousef, Haitham M.K; Al Jaraedah, Abdul Raheem; Alomari, Natheer Mohammad; Al-Qawasmeh, Shireen Ibraheem; Al-Natour, Mouad Mohammed (Journal of World Englishes and Educational Practices, 2025)
This study investigates the motivations and types of code-switching among bilingual Jordanian speakers of Arabic and English. It explores the reasons why these speakers switch between their first language (L1), Arabic, and their second language (L2), English, during interactions. Data are collected through observation and detailed note-taking. A theoretical model is employed to analyze the data and provide an in-depth understanding of this phenomenon. The findings reveal two key aspects of code-switching among the participants. First, code-switching serves distinct motivational purposes, notably expressing identity and self-confidence through the simultaneous use of both languages. Additionally, it compensates for lexical gaps when expressing reactions to others' speech or actions. Second, the study identifies three distinct types of code-switching employed: inter-sentential switching, tag-switching, and intra-sentential switching. Intra-sentential switching is the most frequent (43 instances), followed by inter-sentential switching (29 instances) and tag-switching (21 instances). This research contributes valuable insights into the dynamics of code-switching in a specific bilingual community and recommends future research on the sociolinguistic functions of code-switching in diverse contexts, such as multilingual classrooms, kings and presidents in different settings or media.